Agreement between dual x-ray absorptiometers using pencil beam and fan beam: indicators of bone health and whole-body plus appendicular tissue composition in adult athletes - Tavares,Óscar (2018)
SUMMARY OBJECTIVE: The current study was aimed to examine intra-individual variation on indicators of bone health in addition to whole-body plus appendicular tissue measurements using two concurrent assessments based on pencil beam and fan beam dual energy X-ray absorptiometry (DXA) systems in adult athletes from several sports. METHOD: Thirty-two male participants (27.6±10.1 years) were measured on anthropometry including multifrequency bioelectric impedance and air-displacement plethysmography. Bone mineral content (BMC), bone area, fat and lean soft tissue were derived using pencil beam (Lunar DPX-MD+) and fan beam (Lunar iDXA) absorptiometry. Bone mineral density (BMD) was obtained for the femoral neck, trochanter and triangle of ward. Finally, the right thigh was defined as a region of interest (ROI). Analyses comprised intra-class correlation (ICC), Effect size (d) from mean differences of repeated measurements, coefficient of variation (CV) RESULTS: ICC were >0.900 for all measurements. Intra-individual differences were large for BMC (d=1,312; CV=2,7%), bone area (d=1,761; CV=2,7%), fat tissue (d=1,612; CV=11%) and all indicators of appendicular lean soft tissue (d=1,237-1687; CV=2,0-4,1%). A very large difference (d=4,014; CV=8.4%) was diagnosed for lean soft tissue of the ROI. CONCLUSION: Although differences among concurrent instruments for BMC and bone area, the effect size of mean differences was negligible for BMD. Fat and lean soft tissue derived from DXA should be interpreted as reference values (not criterion) due to equipment-related variation, more apparently in the ROI values.